Positive parenting practices support children at neurological risk during COVID-19: a call for accessible parenting interventions - Green, Rivka; Linga-Easwaran, Janaksha; Goodman, Carly; Taylor, Marin; Fabiano, Giulia F.; Miller, Steven P.; Williams, Tricia S. (Frontiers in Psychology, 2024)
Children and youth with neurological and/or neurodevelopmental conditions were at high risk for behavioral and mental health challenges during the COVID-19 pandemic. Positive and responsive parenting practices may be one way to prevent and manage potential difficulties in families. We aimed to identify whether positive parenting practices were associated with reduced behavioral concerns in children at neurological risk during the late stages and aftermath of the COVID-19 pandemic. In addition, we examined whether ongoing parental stress, anxiety, and depression impacted parenting practices during this time period. Families (N = 179) with children 4 to 15 years old (M = 7.11y, SD = 2.02) diagnosed with neurological (84.3%), neurodevelopmental (54.8%) or comorbid neurological and/or neurodevelopmental conditions (21.2%) were contacted to complete online questionnaires regarding demographics, parent stress, child behavior, COVID-19 conditions, and parenting practices. Multivariable linear regression (MLR) analyses examined the association between positive parenting practices and parenting competency measures with child behavioral outcomes, controlling for relevant covariates, including COVID-19 related stress. MLR were also run to determine whether parental mental health impacted parenting practices. More positive parenting practices predicted fewer child problem behaviors and lower intensity of problem behaviors. Similarly, a higher sense of satisfaction with parenting competence also predicted fewer child problem behaviors and lower intensity of problem behaviors. In addition, higher reported parental depression, anxiety, and stress significantly predicted fewer reported positive parenting practices. Findings points to the promising application of positive parenting interventions to support vulnerable families, as well as the need for parental mental health intervention to support parenting practices.